Prosocial behavior in toddlerhood and early childhood: Consistency across subtypes and over time - Paz, Yael; Davidov, Maayan; Orlitsky, Tal; Hayut, Mor; Roth-Hanania, Ronit; Zahn-Waxler, Carolyn (Frontiers in Psychology, 2023)
Introduction Young children show their capacity for compassion and their desire to enhance the welfare of others in multiple ways. The present study sought to address gaps in knowledge regarding prosociality in the early years. Specifically, the study examined whether different subtypes of prosociality are interrelated, whether they are consistent over time, as well as the meaning of young children’s spontaneous versus cued prosocial behavior. Methods In a longitudinal sample (N = 151), three subtypes of prosocial behavior—instrumental helping, compassionate helping (comforting), and sharing—were assessed using behavioral tasks in toddlerhood (18 months) and early childhood (36 months). Results Consistent with hypothesis, partial convergence was found between the different prosociality subtypes at each age. There was also modest continuity over time, both within and across prosocial subtypes. Moreover, at both ages, when children helped or shared spontaneously, they also provided more assistance in the task. Children’s tendency to assist spontaneously was partially consistent across situations by early childhood. Discussion The findings indicate that a moderately stable disposition toward prosociality is already evident during early ontogeny. Moreover, different subtypes of prosocial behavior are distinct yet interrelated in the early years, suggesting they have both common and unique underlying mechanisms. Lastly, young children’s spontaneous (versus cued) prosocial action appears to reflect both motivational and cognitive processes.